Correlação termográfica em pacientes com síndrome fibromialgica e hipotireoidismo - Costa, Ana Paula Christakis (2022)
This retrospective exploratory study aimed to thermographically correlate the variations in Brown Adipose Fat (BAT), hand, and eyes temperature with the skin temperature of the topographic region of the thyroid in patients with hypothyroidism (HP) and fibromyalgia syndrome (SFM). A total of 136 subjects from 10.000 electronic thermographic medical records were classified into three groups: Group 1 (FM+HP), containing 50 subjects with SFM and PH; Group 2 (FM), with 56 subjects with SFM; Group 3 (Control) with 30 normal subjects without SFM and HP. The thermal images of the electronic medical records were acquired using a FLIR T650SC infrared camera; the dedicated computer program Flir Report was used to demarcate the temperatures of the topographic region of the thyroid, BAT, hands, and eyes, bilaterally; and the temperature data obtained from each Group were statistically analyzed by Microcal Origin 6.0. Analyzing the thermographic results from the dermal region of the thyroid, it was observed that when the thermal correlation of the data was performed, it was obtained that Group 1 (31.7 ± 0.2°C), Group 2 (31.6 ± 0.2°C), and Group 3 (31.9 ± 0.2°C) presented similar mean temperatures among themselves. Pearson’s Linear Correlation Coefficient (ρ) was equal to 0 (zero), meaning that the means of these temperatures are not correlated among themselves. For the BAT, the means of Group 1 (31.6±0.2°C), Group 2 (31.5±0.2°C), and Group 3 (31.5±0.2°C) were similar to each other and the ρ = 1, meaning that the variables, especially for Group 1 together with the BAT, have a positive and strong correlation. For the hands, the means of Group 1 (30.4±0.3°C), Group 2 (29.8±0.3°C), and Group 3 (30.1±0.3°C) statistically were different from each other, and the ρ = 1 for Groups 1 and 3 and zero (0) for Group 2. And finally, the ocular globe tone, the means of Group 1 (31.1±0.2°C), Group 2 (31.4 ±0.3°C), and Group 3 (31.8±0.2°C) are statistically similar to each other. The ρ = 1 for Groups 1 and 3 and zero (0) for Group 2, showing a strong and positive correlation between the regions studied, especially in Group 1. Thus, it was concluded that the temperature variation of the thyroid skin region will be directly proportional to the temperature variation of the brown fat (BAT), the extremities, and the eye. However, the results of this investigation demonstrated that the temperature measurements of the thyroid, BAT, and eye were not statistically different, meaning that a variation in the metabolic activity of the thyroid gland is not dependent on individual condition, whether SFM and/or HP is manifested. Therefore, environmental, physiological, and pathological factors should be investigated in order to further investigate whether the temperature variation of these regions may trigger the symptoms of GP or PH. Further studies should be carried out on the impact of environmental, physiological, and pathological issues in each subject that presents concurrent symptoms of HCM and PH and associate the application of thermography to elucidate all the hypotheses that may arise on the subject.